Incidence and Predictors of Delirium After Cardiac Surgery - Bajracharya, Smriti Mahaju; Baidya, Rabin; Bhandari, Sandip; Amatya, Ashish G (Journal of Nepal Health Research Council, 2023)
Background: The overall purpose of this study was to determine the incidence and perioperative factors that predispose to cause delirium in postoperative cardiac surgery patients in our Intensive Care Unit. Methods: We performed a prospective, observational study. Following institutional review board approval, this study included 234 patients above the age of 18 years meeting the inclusion criteria for cardiac surgery in Shahid Gangalal National Heart Center from July 2018 to December 2018. Preoperative, intraoperative and postoperative data for possible risk factors were obtained. Daily assessment of delirium was done during Intensive Care Unit stay of the patient. Collected data were analysed by means of statistical software SPSS-21. Results: The incidence of delirium was 15.6% (35/224) in our study. Delirium was seen in 14 out of 58 (24.1%) patients with age >60 years which was found to be statistically significant. Preoperative risk factor for developing delirium were carotid artery disease and Hemoglobin level <10gm/dl. Intraoperative risk factor for developing delirium were blood transfusion, longer cardiopulmonary bypass time. Post-operative factors for developing delirium included longer Intensive Care Unit stay, mechanical ventilation time ,duration on inotropes , blood transfusion, use of non-invasive ventilation, sleep deprivation, use of intra-aortic balloon pump, Pao2<70. Conclusions: As shown in our study, delirium is a frequent occurrence in the cardiac surgical population. The incidence of delirium after cardiac surgery was 15.6%. Several risk factors pre-operatively like age>60 years, carotid artery disease, Hb<10gm/dl, intra-operative factors like longer cardiopulmonary bypass time, blood transfusion and post-operatively longer duration of Mechanical ventilation, Intensive Care Unit stay, blood transfusion, use of intra-aortic balloon pump and Non-invasive ventilation were found to be predictors of delirium. Keywords: Keywords: Cardiac surgery; delirium; risk factors